Corpus-based error analysis of written works in Chinese by Spanish students - Shiyang, Liu (Sinología hispánica. China Studies Review, 2021)
With the popularity and development of learning the Chinese language in Spain, more and more students are choosing to study Chinese as a foreign language. However, due to various factors -interlinguistic and intralinguistic factors-, students have many difficulties during the learning process and they make numerous mistakes of expression. This article proposes to carry out a quantitative and qualitative analysis of the different errors that the students commit, from the lexical, sentence and discursive perspectives. This analysis will be carried out from a corpus of written works in Chinese by Spanish students, and from this analysis we obtain the following main results: errors are concentrated at the lexical and sentence level while at the discursive level the amount of errors is less; at level A1 the interlinguistic factors occupy a predominant place in causing mistakes, and as the level of Chinese rises, intralinguistics factors begin to play a more important role; from level A1 to level B1, we detect certain elements with a tendency to fossilization.